2010
DOI: 10.1007/s00432-010-0952-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with TRAIL and PPARγ ligands overcomes chemoresistance of ovarian cancer cell lines

Abstract: Therefore, the combinational treatment with TRAIL and PPARγ ligands might be a promising experimental therapy because the PPARγ ligands, especially d15-PGJ(2), sensitize drug-resistant ovarian cancer cells to TRAIL-induced apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
1
22
0
1
Order By: Relevance
“…Studies have shown the antineoplastic effects of PPARγ ligands in various preclinical models (51); however, agonists of these receptors used as monotherapy failed to exert therapeutic benefits in advanced stage breast patients (52). Notably, PPARγ agonists in combination with the conventional antineoplastic drugs, such as carboplatin or tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), showed synergistic effects, indicating that differentiation induced by PPARγ activation restored sensitivity to the cytotoxic drug (53,54). These synergistic effects were replicated in cells treated with DOX + I 2 in both preclinical (16) and clinical studies (17), supporting the notion that some I 2 effects are mediated by PPARγ activation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the antineoplastic effects of PPARγ ligands in various preclinical models (51); however, agonists of these receptors used as monotherapy failed to exert therapeutic benefits in advanced stage breast patients (52). Notably, PPARγ agonists in combination with the conventional antineoplastic drugs, such as carboplatin or tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), showed synergistic effects, indicating that differentiation induced by PPARγ activation restored sensitivity to the cytotoxic drug (53,54). These synergistic effects were replicated in cells treated with DOX + I 2 in both preclinical (16) and clinical studies (17), supporting the notion that some I 2 effects are mediated by PPARγ activation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, weight gain or bone fractures observed in response to administration of PPARγ agonists 187190, 206 might be offset by agonist activity for PPARα or PPARβ/δ, which can increase lipid catabolism and stimulate osteoblast activity in bone 208 . As there is also good evidence that combining PPAR activation with other chemopreventive or chemotherapeutic agents can significantly increase anti-cancer activities 92, 209220 , it remains possible that dual or pan PPAR agonists could lead to even greater improvement in efficacy.…”
Section: Ppars and Cancer Treatment And Preventionmentioning
confidence: 99%
“…TRO treatment showed no effect on proliferation on its own; however, when combined with TRAIL, that reduced cell numbers in etoposide-, pemetrexed-, cisplatin-, docetaxel-, and gemcitabine-resistant cell lines. Similarly, 15d-PGJ 2 treatment inhibited growth in all cell lines, especially the HEY cell line which was developed by the authors [43]. …”
Section: Cell Signaling Moleculesmentioning
confidence: 99%